Laser diodes optical output power model. (February 2019) - Borràs, Ramon; del Rio, Joaquin; Oriach, Carles; Juliachs, Jordi
Highlights: Laser diodes optical output power, mathematical and Pspice modelling. Optical output power temperature modelling. Slope efficiency temperature dependency hypothesis and confirmation. Cold measurement method avoiding temperature effect in the optical power measurement. Laser diodes optical output power automatic characterization system. Abstract: This article proposes a modelling method of laser diodes optical output power, especially for mid-high power diodes working in continuous wave (CW) or quasi continuous wave (QCW) modes, and focusing in the optical output power dependency on temperature and its model implementation in Pspice, targeting its computer simulation. It is commented the theory and related mathematical expressions used in the model, the Pspice program model and the purpose of its different parts, and how mathematical expressions are introduced in it. It is proposed a diodes optical output power response characterization method using an automatic data acquisition system to obtain diodes response curve avoiding temperature effects during the measurements. Implementation example of the modelling and characterization method in a laser diode, model results versus real measurements comparison and related conclusions are exposed.